Nurse Perceptions of Babywearing for Neonates With Neonatal Abstinence Syndrome in the Neonatal Intensive Care Unit. (February 2021) - Williams, Lela Rankin; Grisham, Lisa M.; Gebler-Wolfe, Molly; Kelsch, Karen; Bedrick, Alan; Bader, M. Y.
Abstract : Background: Infants diagnosed with neonatal abstinence syndrome (NAS) often spend several weeks in a neonatal intensive care unit (NICU) and have difficulty being consoled. Infant carriers may be used to help with irritability, while allowing the adult user to be more mobile, through the practice of babywearing (the facilitated holding of an infant using a soft cloth infant carrier worn on the body). Purpose: To examine the experience of babywearing infants diagnosed with NAS while admitted in the NICU from the perspective of the nurses who care for them. Methods: Nurses (N = 18; mean age = 35.44 years, SD = 9.45) were recruited and interviewed using a semistructured interview method from a 38-bed NICU in the Southwestern United States. Results: A thematic content analyses using an open coding scheme yielded 6 themes that fell into 2 categories: (1) benefits of babywearing infants with NAS in the NICU (Infant Consoling, Adult Multitasking, Caregiver–Infant Trust); and (2) suggestions to maximize babywearing in the NICU (Infection Control, Reoccurring Infant Carrier Education, and Reduced Patient Load). Implications for Practice: Many NICUs incorporate kangaroo care (or skin-to-skin contact) as a treatment option; however, NICU staff cannot participate in kangaroo care. Babywearing is a practical alternative for nurses and support staff. Nurses supported the practice of babywearing as a means to improve the well-being of infants with NAS while also allowing for increased efficiency in nursing tasks. Implications for Research: More prospective studies are needed that evaluate the carryover effects and long-term impact of babywearing for infants diagnosed with NAS.